2016
DOI: 10.1002/2016wr019040
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional flow structure and bed morphology in large elongate meander loops with different outer bank roughness characteristics

Abstract: Few studies have examined the three‐dimensional flow structure and bed morphology within elongate loops of large meandering channels. The present study focuses on the spatial patterns of three‐dimensional flow structure and bed morphology within two elongate meander loops and examines how differences in outer bank roughness influence near‐bank flow characteristics. Three‐dimensional velocities were measured during two different events—a near‐bankfull flow and an overbank event. Detailed data on channel bathyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
46
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 27 publications
9
46
0
1
Order By: Relevance
“…Differences in roughness are examined when the banks are inundated and not inundated. Previous work on the two bends has examined the mechanisms that lead to mass failure of the outer banks (Konsoer et al ., ) and the spatial pattern of flow structure through elongate bends at different stages (Konsoer et al ., ), The present article extends this previous work by providing insight into spatial variation in characteristics of outer bank roughness for elongate bends along large meandering rivers and differences in bank roughness characteristics for subaerial versus subaqueous conditions. This knowledge supports efforts to link roughness characteristics with near‐bank flow conditions, both in the field and in numerical models of large meandering river systems.…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…Differences in roughness are examined when the banks are inundated and not inundated. Previous work on the two bends has examined the mechanisms that lead to mass failure of the outer banks (Konsoer et al ., ) and the spatial pattern of flow structure through elongate bends at different stages (Konsoer et al ., ), The present article extends this previous work by providing insight into spatial variation in characteristics of outer bank roughness for elongate bends along large meandering rivers and differences in bank roughness characteristics for subaerial versus subaqueous conditions. This knowledge supports efforts to link roughness characteristics with near‐bank flow conditions, both in the field and in numerical models of large meandering river systems.…”
Section: Introductionsupporting
confidence: 75%
“…This material is capped by 1–2 m layer of fine silty‐sand loam that produces a nearly vertical bank face. In the downstream part of the bend, erosion along the outer bank has exposed a local outcrop of interbedded shales and sandstones of the Carboniferous Pennsylvanian Bond Formation (Konsoer et al ., ). Vegetation along the outer bank is confined mainly to the top of the bank.…”
Section: Field Sitementioning
confidence: 97%
See 2 more Smart Citations
“…Uniformly vegetated banks can significantly reduce near-bank velocities along entire river bends (Konsoer et al, 2016a). At a smaller scale, Pizzuto et al (2010) suggested that the joint effect of nearby trees on flow detachment could reduce erosion rates similarly to small-scale roughness (Kean and Smith, 2006), based on short-term observations of sequential abutments on sandy-loams.…”
Section: Effects Of Tree Roots On Bank Erosionmentioning
confidence: 99%